Drug release, cytocompatibility, bioactivity, and antibacterial activity of doxycycline loaded Mg-Ca-TiO2 composite scaffold. (5th February 2018) - Bakhsheshi-Rad, H.R.; Hamzah, E.; Staiger, Mark P.; Dias, George J.; Hadisi, Z.; Saheban, M.; Kashefian, M.
Abstract: Mg-Ca-TiO2 (MCT) composite scaffolds loaded with different concentrations of doxycycline (DC) with a network of interconnected pores with good compressive strength (5 ± 0.1 MPa) were fabricated via space holder method for the first time. The results showed that MCT-DC scaffolds possess a porosity and pore size in the range of 65–67% and 600–800 μm respectively. The bioactivity results exhibited the apatite formation on the MCT-DC scaffold surface, indicating that DC did not obstruct the bioactivity of MCT. The MCT-DC scaffolds drug release profiles show the initial burst and sustained drug release (55–75%) and the release rate could be adjusted via altering the DC concentration. The MCT loaded with 1 and 5% DC did not indicate cytotoxic behavior against MG63 cells while further DC loading resulted in some toxicity. Antimicrobial properties of MCT-DC scaffolds against Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ) bacteria were examined and the results reveal oblivious inhibition zone around each MCT-DC scaffold whereas no obvious inhibition is observed around the MCT scaffold. Therefore, MCT-DC composite scaffolds with low concentration of DC could be alternative candidates for infection prevention and bone tissue engineering. Graphical abstract: Highlights: Mg-Ca-TiO2 composite scaffold loaded with different concentrations of doxycycline were prepared by space holder method. Mg-based scaffold containing doxycycline possesses compressive strength of 5 MPa with porosities of 65%. Antimicrobial activity of the composite scaffold increased with increasing doxycycline concentration. Mg-based composite scaffolds containing low concentrations of doxycycline showed good biocompatibility. These composite scaffolds showed good biological properties and desired drug release trend for bone infection treatment.